Revisiting debt-led and export-led growth models: A sectoral balances approach - Jan Behringer; Till van Treeck (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2018)
In this paper, we revisit the macroeconomic foundations and political economy of national growth models. We challenge the Kaleckian framework underpinning the emergent growth model literature in comparative political economy, which focuses primarily on the functional income distribution (wages versus profits), while ignoring personal income distribution (inequality across private households). Using the examples of the "export-led" and "debt-led" growth models of Germany and the United States, we show how institutional differences can help explain why different countries developed different patterns of income distribution and how income distribution and institutions interacted to generate financial imbalances in different sectors of the economy (i.e., the private household sector, the private corporate sector, and the government sector). – – In diesem Working Paper setzen wir uns mit den makroökonomischen Grundlagen und der politischen Ökonomie von nationalen Wachstumsmodellen auseinander. Wir hinterfragen den Kaleckianischen Analyserahmen, welcher der neuen Literatur zu Wachstumsmodellen in der vergleichenden politischen Ökonomie zugrunde liegt. Dieser konzentriert sich hauptsächlich auf die funktionale Einkommensverteilung (Löhne versus Gewinne), während die personelle Einkommensverteilung (Ungleichheit zwischen den privaten Haushalten) vernachlässigt wird. Anhand der "exportgetriebenen" und "schuldengetriebenen" Wachstumsmodelle in Deutschland und in den Vereinigten Staaten zeigen wir, wie institutionelle Unterschiede zur Erklärung von unterschiedlichen Entwicklungen in der Einkommensverteilung beitragen können und wie Einkommensverteilung und Institutionen interagiert haben, um Ungleichgewichte in verschiedenen Sektoren der Volkswirtschaft (d.h. dem Haushaltssektor, dem Unternehmenssektor und dem Staatssektor) zu erzeugen.
urn:nbn:de:101:1-2018102513450281964217
Keywords: D3; J5; P5; 330; Growth models; financial balances; functional income distribution; personal income distribution; institutions